2010
DOI: 10.3758/brm.42.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Exploring lexical co-occurrence space using HiDEx

Abstract: This work investigates a class of models of lexical semantics derived from the hyperspace analog to language (HAL; Burgess, 1998;Burgess & Lund, 2000), a computational model of word meaning that derives semantic relationships from lexical co-occurrence. Although the original HAL model was well specified, it contains several parameters whose values were set without formal or empirical justification. We have created a novel and freely available implementation of the HAL model-called High Dimensional Explorer (Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 32 publications
(73 reference statements)
4
144
0
Order By: Relevance
“…However, the idea that semantics can be expressed as a dimensioned space has not. Recent work with co-occurrence models of lexical semantics can be viewed as a technologically updated extension of much of Osgood's earlier work (e.g., Durda & Buchanan, 2008;Jones & Mewhort, 2007;Landauer & Dumais, 1997;Lund & Burgess, 1996;Rohde, Gonnerman, & Plaut, 2006;Shaoul & Westbury, 2010). Although their technical details vary, all of these models work from the basic assumption that the surrounding context of a word is informative of its meaning.…”
mentioning
confidence: 99%
“…However, the idea that semantics can be expressed as a dimensioned space has not. Recent work with co-occurrence models of lexical semantics can be viewed as a technologically updated extension of much of Osgood's earlier work (e.g., Durda & Buchanan, 2008;Jones & Mewhort, 2007;Landauer & Dumais, 1997;Lund & Burgess, 1996;Rohde, Gonnerman, & Plaut, 2006;Shaoul & Westbury, 2010). Although their technical details vary, all of these models work from the basic assumption that the surrounding context of a word is informative of its meaning.…”
mentioning
confidence: 99%
“…Given that one of the aims of this study was to compare the performance impact of retaining stripped affixes as context dimensions, a larger window size was deemed appropriate (i.e., to handle inflected word forms with more than one prefix, like unpremeditated [un+ pre+ meditate +ed], or more than one suffix, like computerization [compute +er +ize +ation], while still capturing cooccurrences with adjacent words, which could also be surrounded by their own stripped affixes). Levy (2007, 2012) found that window sizes of up to three words in either direction still performed very well (i.e., major drops in performance were not noted in most of the tasks until reaching window sizes of four or five), and Shaoul and Westbury (2010) found that a window size of five words in either direction (using a linear ramp weighting scheme) led to optimal performance in a lexical decision task (also used in this study). We chose a window size of four words in either direction to accommodate affix retention, while minimizing the trade off in performance.…”
Section: Co-occurrence Model and Parameterizationmentioning
confidence: 69%
“…The High Dimensional Explorer implementation (HiDEx; Shaoul & Westbury, 2010;, an extension of HAL, was developed to address three major shortcomings of HAL. First, despite its vector normalization, HAL is prone to the influence of strong orthographic word frequency effects on vectors and vector distances (Shaoul & Westbury, 2006), and HiDEx uses improved vector normalization schemes to counter these effects.…”
Section: Corpus-based Semantic Space Modelsmentioning
confidence: 99%
See 2 more Smart Citations